The efficacy of art therapy: a comparative study of primary school children in Macau - Vai, Man Kei (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

Meditation practice: impact on the quality relationships, level of psychological distress, anxiety and depression - Baldinho, Gloria (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Temperament and motive disposition as predictors of academic emotions - Choi, Lik Hang (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Gambling motivation, gambling behaviors, alcohol use and substance abuse among Macau casino workers - Coteriano, Carla (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Relationship between personality factors and anger among Chinese female population in Macau - Lijadi, Anatasia Aledelina (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Self construal and cross-cultural adjustment among Filipino migrant workers in Macau: the mediating role of communicative adaptability - Mordeno, Emelyn R. (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Parenting on depression: the mediating role of self-esteem - Noronha, Cintia Chan De (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Mental health and sociodemographics profile as predictors of eating attitude - Pereira, Patricia Teresa (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Bullying, victim and pro-social behaviors as predictors of mental health among primary students - Vong, Maria (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The influence of socialiration tactics and causality orientations on eross-evltuaal adjustment - Bilugan, Marifi Lagan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The influence of social companions on affect and life satisfaction - Chao, Hang In (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Crisis in motivation: exploring the factor structure of academic amotivation among school student in Macau - Chao, Josefina (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Academic emotions as mediators between achievement goals and academic: achievement - Kot, Sok Kuan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The efficacy of self-control training in the Macao youth correctional institute: changes in the impulsiveness and emotion stability of young offenders - Lei, Joana (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Gender differences in self-reported depression: an examination of gender bias, social desirability and stereotype threat - Ng, Lai Va (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

General affective dispositions on academic emotions: exploring the general and specific dimensions of emontions as determinants of students' emotional experiences - Oberhauser, Petra (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A proposed young persons community center for prevention and intervention program for vulnerable young persons - Olivena, Qlinto (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Exploring the therapeutic value of dancing among the selected Chinese women in Macau - Rosario, Elzira Jonas Do (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The influence of parental expectations on the psychological distress of Chinese college students in Macao - Sam, David (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Public and family stigma of seeking psychological help among Chinese college students - Sou, Kuai Long (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Achievement goals, academic motivation and academic emotions - Sun, Sok U. Rosa Maria (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Academic self-concept and non-academic self-concept on test anxiety: the mediating role of academic emotions - Tam, Chi Kuan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Academic self-concept and non academic self concept on test anxiety the mediating role of academic emotion - Wong, Nga Na (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The efficacy of an empathy training program for young offenders in the Macao youth correctional - Wong, Pak Kei (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The outcome of mind over old-age depression program on order people with depression in one Macao elderly day center - Yang, Liu (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Exploring the dynamics of students with social anxiety through multiple case studies: a proposed intervention program - Cabral, Olga Tsvirkun De Freitas (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Attachment styles and adjustment as predictors of academic emotions among Macau college students (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Bibliotherapy with the Chinese oracle using the i ching to promote insight - Davis, Adrian John (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relationship between work engagement, meaning in life, satisfaction with life and happiness - Lau, Kin Hong (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

School environment’s influence on academic emotion - Lei, Weng Tong (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Achievement goals on school engagement: looking at the mediating role of academic emotions in Chinese secondary school students - Leong, Sin U. (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relationship between music preference, relaxation and personality: a study of Macau residents - Pun, Nga Si (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Psychological health components as predictors of academic emotions - Sin, Wai Wun (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Job stressors, psycholiogical capital, burnout and work engagement among hotel-casino office workers - Sng, Woei Tyng (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Treanch model of reciprocaion: relating,achiement goals, engagement and academic emotions - Vong, Ka Iu (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Psychological well-being and clinical symptoms as determinants of intuitive eating - Xavier, Elisa Maria (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Stress, depression and anxiety on gambling behavior: the mediating role of gambling related cognition - Chan, Ka Wa (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Loving music: an analysis on the latent structure of students' reasons in wanting to learn music - Choi, Sin Va (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relationship between personality, locus of control and driving anger - Fok, Celia Machado (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Perceived benefits of long-term iyengar yoga practice - Ho, Canossa (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Amotivation in learning mathematics: the taxonomy of why secondary school students in Macau are not motivated to learn mathematics - Iam, Man Cheng (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Self-regulation on gambling intention: the mediating role of injunctive norms - Ian, In Tong (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Academic emotions and achievement goals as predictors of academic achievement - Kong, Hou I. (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Effectiveness of mind over old-age depression (mood) programme for older persons in Macau - Lam, Chao Ut (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Post-migration stress and mental health of Filipino female domestic workers in Macau: the moderating role of social networks - Mendoza, Norman B. (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Motivation in learning science in the context of Macau secondary school students: understanding the taxonomy of academic motivation in science learning - Mok, Sao Kuan (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Third culture kids: their search for cultural identity - Oliveira, Deborah Christina de (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Stages on change: exploring the transitions of heroin using the trans theoretical method - Wong, Ka Wo (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Cyber - bullying in Macau schools: an exploratory study - Afshar-Tongga, Mona (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Sports motivation of adults with motor disability in Macau - Castilho, Leonardo Luís (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Examining the efficacy of outdoor education camp in enhancing middle school students' self-esteem - Chan, Chi Hong (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Chinese values and perception of professional counselling service: a study among senior high school students in Macau - Chan, Pan Kei (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Perceived motivation of telephone counseling volunteers in Macau - Chao, Weng Man (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A study of the risk of burnout in final year nursing students in clinical practicum - Cheong, Chan Long (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The effectiveness of a Macau drug prevention program: a comparative Study - Cheung, Claudia (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

Influence of parents and peers on stress and coping in Korean-born adolescents in Macau - Choi, Dong Jin (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The health related quality of life of coronary heart disease patients with and without percutaneous coronary intervention - Chu, Mei I. (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Conflict resolution among adolescents in Macao - Fong, Kit Leng (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Responsible gambling among casino staff in Macau – a pilot study - Ip, Chi Hou (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The influence of job satisfaction and coping strategy on turnover intention of employees in Macao - Kong, Wan Si (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Learning strategies and students adaptation to college: a mixed methods research in higher education institutions - Kwong, Ho Keung (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relationship between effort/reward imbalance and happiness: a study of Macau residents - Lam, Hoi Man (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Academic disengagement in learning science among Macau secondary school students: looking at the taxonomy of science learning amotivation - Lam, Sok I. (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Academic support and belongingness and academic achievement mediated by academic motivation - Lao, Wai I. (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The meaning of faith: an inquiry of the perceptions of evangelical Christians in Macau - Lei, Ut Neng (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Relationship between depression, sleep quality and levels of physical activity in Macau adult population - Leong, Petra (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

優質睡眠與工作壓力對澳門博彩員工之相關性研究 = Quality of sleep and work-related stress among casino employees in Macau - Ng, Kuan Fun (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The work stress and well-being of casino hotel executives in Macau - Ong, Irene (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Pre-marital counseling: the experience of Chinese Christian couples in Macau - Pun, Oi Kuan (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Mianzi: uncovering its roles in Chinese people's way of living - Tang, Junhui (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relationship between traditional Chinese beliefs and help seeking intention: a survey of elderly people in Macau - Wong, Ka Lok (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Exploring the quality of life of Macau people with visual impairment - Wong, Ka Meng (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Correlation of emotional intelligence, sports emotions, and coping strategies among Chinese adolescents in Macau - Yuen, Po Shan (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A discussion on the group psychotherapy treatment for depressed individuals - Chan, Ka Chon (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Exploring attitudes concerning family size in Macau: a qualitative study - Ho, Nga Si (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The perception of psychological counseling services in Macau: the influence of the Chinese culture of "face" - Lai, Chi Shan (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Gratitude interventions: the person-activity fit dimension - Todd, Philip (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Relapse prevention: a reflection around high-risk situations, self-efficacy and life-style modifications in substance abusers - Bucho, Marta (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The effect of family and personal factors on marital attitudes and expectations in Macau - Chan, Cheng Nga (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Pathway to drug addiction among Macau teenagers - Cheang, Tat Hin (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Exploring occupational stress and job satisfaction among pharmacists in Macau - Ho, Joel (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The impact of social support on the mental health of the visually impaired in Macao = 社會支援對於澳門視障人士的心理影響 - Loi, Wai Cheng (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Attitudes towards counseling between iran and Macau universities students - Rashinia, Jafar (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Drug abuse among adolescents in Macau: its psycho-socio-cultural perspectives - Song, Yi Xuan (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relationship between time perspective and study motivation on decision making of student in Macau - Tong, I Wan (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

The relationship between children's attachment with parents and general self-efficacy during young adulthood in Macau - U, Lei Fong (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Effects of family closeness and conflict on young adults' peer relationships - Chan, Mei Kei (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Interpreting the causes of depression in Macau elderly - Kwok, Wing Yee (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Study of everyday moral reasoning of senior secondary students in Macao - Ng, Sio Lin (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

"Adolescents' psychological well-being from diversed family types and functioning in Macao" - Tou, Ka Man (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The psychological factors related to the usage of electronic devices among adolescents in Macau - Chan, Ka Pou (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The use of cognitive behavior child-centered play therapy: a case study - Cheong, Tania Guilherme (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Adolescent pathways to hikikomori in Macau - Hon, Leng Ian (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Family constellations: a systematic review and a critical analysis - Kuan, Man Sok (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Perception and insight on the psychological and environmental risk factors contributing to first time drug use among young adults in Macau - Lei, Hon Nei (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Conceptions of giftedness in Macau - Leong, Nga Ut (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Effects of parenting styles, parent expectations, and academic results on Macau adolescent's self-esteem - Mak, Chi Kwan (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The role of spirituality and religion in counseling and pyschotherapy of christian clients - Tse, Chau Hung (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Promoting positive peer pressure through small group peer interaction - Vargas, Maria Chrislina Bondoc (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A vignette: study do casual explanation and continuum beliefs affect Macau college students' attitudes towards mental disorders? - Wong, Ka In (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Parents views on special education in Macao - Wong, Man Wa (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Impact of internet usage, demographic factors, and illusory perched control on pathological gambling, depression, anxiety and stress - Au, Ho Ki (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Leisure time and well being of elderly in Macau - Dias, Anabela Maria (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relevance of philosophy, spirituality and religion in counselling & psychotherapy within Asia - kazmi, Sayed Shajaat Hussain (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Comparing student's learning satisfaction in lower secondary and upper secondary school education - Kong, Weng Mei (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The parenting style and quality of attachment in Portuguese vs. Chinese families - Kuoc, Lai Sam (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Stress and coping of the high school students in Macau: factors and solution - Leong, Ka Chon (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Urge to End It All: A Closer Look into Suicidal Thoughts & Behaviors - Linyu, Khriesizou; Lau, Christine (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The influence of culture on psychological help-seeking behavior: a study with the Filipino community in Macao - Zancan, Madalena (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Couple Satisfaction in Partners of Male Shift Working Pilots - Bredenhann, Andri (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Impacts of Burnout and Work Engagement on Performance: a Study of a Surveillance Team - Chang, Pou I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Rewriting Life Story and Career Development: a Case Study Using a Narrative Approach - Choi, Ka Lok (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Biculturalism and Parenting Styles among Filipino Mothers and Young Adult Offspring in Macao - Doctor, Ana Catarina Alvarez (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Effectiveness of Art Therapy for Children with Special Educational Needs - Ho, Weng Chong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Effect of Peers, School Connectedness, Parents on Internet Gaming Addiction in Adolescents - Ip, Tan Long (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Children's with SEN Views About Their Experience in Inclusive Education - Lai, Hoi Lam (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Analyzing Intercultural Romantic Relationships of Filipinos in Macao: Informing Counseling Strategies - Li, Anne Michelle Sia (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Hypnotherapeutic Treatment as a Way to Enhance Sleep Quality: Case Study on a Clinical Counseling Professional in Macao - Li, Hiu Yung (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Parenting Training for Enhancing Self-Esteem, Self-Efficacy, and Emotional Regulation of Mothers Who Were Victims of Domestic Violence - Lou, On I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Family Life Cycle and Number of Children in A Family Affecting Parent’s Parenting Style, Parental Stress, Life and Marital Satisfaction - Mak, Chong Hin (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Quality of Life and Wellbeing of the Foreign Communities in Macao - Mohr, Silvia Isabel (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Teacher Burnout: Applying the Job Demands and Resources Model in Macao - Ng, Kun Keong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Caregivers of Persons with Neurodevelopmental Conditions: Understanding Their Perspectives of the Need of Clinical Counselling Intervention - Pagdanganan, Paula Ramos (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Trend and Characteristics of Deviant Behavior of Young People in Macao Between 2001 and 2019 - Sam, Lek I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Post-Divorce Parent-Child Relationships Impacts and Coping Mechanisma: Qualitative Study In Macao - Vong, Iek Chong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Father’s Involvement and Parenting Styles in Macao - Chan, Ieng Chong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Existential Psychotherapy and Irvin D. Yalom’s Perspective: A Systematic Literature Review - Chan, In Leng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Influence of Parenting Styles Across Generations in Chinese Families in Macao - Chan, Lai Teng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Family Support, Job Insecurity, Coronavirus Stress and Leadership Styles Effects on Burnout and Work Engagement in Hospitality during Covid-19 Pandemic in Macau - Chang, Pou I. (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

The Understanding and the Attitudes Toward Life Education Among Macau Citizens: A Case Study - Che, Iok Seng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The Mediation Effect of Organisational Commitment on Job Autonomy and Turnover Intentions - Cheong, Lai Ieng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

The Mediating Role of Empathy on the Impact of Perceived Parenting Styles on Prosocial Behaviors of Adults - Hoi, Mei Pui (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Parental Involvement and Child Development in Macao: Association with Family Income, Parental Education and Working in the Gambling Industry - Kung, Hang I (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Association Between Early/ Emerging Adult-Parent Attachment and Problematic Internet Use Among College Students in Macao - Lao, Sio Mei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

An Exploration of Building Up the Quality Parent-Child Relationship in Childcare Service in Macao - Leong, On Na (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Parental Stress and Family Relations in Macao: The Mediating Role of Parenting Styles - Siu Kuan Lei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Positive Approach in Preventing Depression in Adolescents: Comparing Local Chinese and Filipino Migrant Adolescents in Macao - Tejada, Anali Jane Gabala (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Experiences and Reflections Related to Mental Health Among University Students during Covid-19: A Case Study - Tou, Un Ieng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Role of Cognition as a Mediator for Narcissism and Trait Aggression as Predictors of Aggressive Driving Behavior - Van, Hou Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Roles and Functions of Social Worker Within Crisis Management of the Pandemic COVID-19 in Long-Term Care Facilities of Macau: A Case Study - Wong Oi Lin (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Social Integration and the Screening of the Early-Stage Dementia in Older Adults: The Mediation Role of Mental Health - Wong Wai Hong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

認知情緒調節策略在澳門家長的童年創傷經驗與專制式教養模式之間的中介作用 =: Childhood Trauma on Authoritarian Parenting among Macao Parents: The Mediating Role of Cognitive Emotional Regulation Strategy - Wong, Ka Kei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Maternal Postpartum Experience in Macao: The Relationship Between Demographics, Income, Social Support and Postpartum Depression - Bonthuis, Ana Maria Barradas Leitão Abril (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Work-Life Balance and Life Satisfaction in Macao: The Mediating Effect of Work Satisfaction - Chan, Lok Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

An Investigation on Macao Children with ASD and their Families needs on Social Support - Chau, Chin Fong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

從混合性研究中探討澳門長者對睡眠健康認知及其相關之因素 =: Exploring Perception on Sleep Health and its Related Factors among Older People in Macau - A Mixed Methods Study - Cheang, Ka Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The Relationship Between Stress and Emotion Regulation with Students’ Academic Achievement - Cheong, Sin Teng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門年輕群體對性別多元態度與態度構成因素之研究 =: The Attitude of the Relative Influential Factors and Gender Diversity on Youth in Macau - Fion, Si Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Art-Based Intervention For Children with ADHD: Catina Fong Chi Cheng - Fong Chi Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Moderating Effect of Job Alternatives Perceptions in the Relationship Between Burnout and Turnover: A Study During the COVID-19 Pandemic in Macao - Fong, Sut Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

The Association Between Interpersonal Relationships and Mental Health in College Students in Macao - Guo, Peiling (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門已婚人士的婚姻質量與社交媒體參與之研究 =: The Study of Marital Quality and Social Media Engagment Among Married People in Macau - Ho, I. Mei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The Indirect Effect of Job Insecurity and COVID-19 Induced Stress on Mental Health through the Mediating Effect of Burnouts and the Moderating Effect of Perceived Social Support among Macau Gaming Employees - Hoi, Lok (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

初探澳門更生人士在專業工作過程的成功因素=: Explore Successful Factors in Recognition of Professional Work Process for Ex-Offenders - Ip, Ka I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The Influence of Strengths-Based Intervention to Students’ Engagement and Self-Efficacy in Macau - Jr. Tabilas, Faustino T. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

Problematic Internet Use and Subjective Wellbeing Among University Students in Macao - Kam, Chi Fat (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Intention Towards Online Counseling among Service Provider in Macau=: 澳門社會服務提供者對應用線上輔導的意向 - Lao, Hoi Keong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The Impact of Father-Adolescent Relationship on Child Development in Macao - Lao, Pak Lun (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門長者對樂齡科技的感知及應用動機研究 =: Elderly's Perception and Motivation for the Application of Gerontechnology in Macau - Lee, Hou Sun (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Moral Self-Regulation or Consistency: The Role of Cultural Values and Workplace Status - Leong, Kin Hei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

澳門中年男士焦慮狀況、求助態度與自殺意念之相關研究 =: A Correlational Study Between Anxiety and Help-Seeking Attitudes on Suicidal Ideation of Middle-Aged Men in Macau - Lo, Kuan U. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The relationship between social support and death anxiety among elderly living alone in Macao - Lo, Pou Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Career Development of People with Physical or Sensory Impairments in Macau - Ma I Mei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Job Satisfaction, Dilemmas and Causes of Hearing Impaired People in Macau =: 澳門聽障人士工作滿意度、困境及其原因 - Pang, Wan I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The Impact and Attitude of Urban Renewal on Citizen Residents in Macau - Si Cheng Iok (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The Effects of an Aikido Based Psychological Intervention Program in Workplace Stress - Tam, Heng Kun (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Applying Social Skills Improvement System Intervention Guide to Primary Students with ADHD and Problem Behaviors in Macau: A Case Study - Ung, Hou Cheang (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

The Relationship Between Work-Life-Balance and Burnout: Effect of Gender and Sector of Activity - Vai, Han Kuoc (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

澳門露宿者服務社工在新冠疫情情間的工作與挑戰 = The Opportunities and Challenges Facing Macau Social Workers Who Work with Homeless People During the Pandemic of 2020 : A Case Study - Wong, Choi Leng (University of Saint Joseph, 2022)
Edition: The Opportunities and Challenges Facing Macau Social Workers Who Work with Homeless People During the Pandemic of 2020
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

A Study on Spiritual Well-Being of Secondary School Teachers in Macau - Wong, Kuan Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Parental Stress and Marital Satisfaction in Macao: The Mediating Effect of Parental Involvement - Wong, Pek Ieng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Effects of Family Support, Friends Support, Supervisor Support, Co-worker Support, and Organizational Support to Resilience and its Effects to Work Engagement - Wong, Sio Peng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

The Effect of Organizational Justice on Work Engagement Between Foreigner and Local Workers in Macau: The Moderating Effect of Organizational Commitment - Wong, Wai Fai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

CASE STUDY ON ART INTERVENTION WITH CHILDREN WITH AUTISM SPECTRUM DISORDER - Wu, Hoi Pio (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

THE RELATIONSHIP BETWEEN INTERNALISING PROBLEMS, ACADEMIC ACHIEVEMENT, SCHOOL ADAPTATION, AND GENDER, AS VIEWED FROM THE PERSPECTIVES OF BOTH TEACHERS AND STUDENTS - Ao, Hoi Ian (University of Saint Joseph, 2023)
The present study aimed to analyse the differences in the internalising problems (anxiety, depression, somatic complaints), assessed by different informants (teachers and students), according to the level of academic achievement and school adaptation level in secondary students. Furthermore, we examine the gender difference in the level of internalising symptoms. Finally, we analyzed the differences between teacher-rated and adolescents' self-reported internalising symptoms. The Achenbach System of Empirically Based Assessment (ASEBA) was used for collecting informants’ data. The sample consisted of 882 secondary students (349 males and 473 females), while 50 came from public schools and 772 from private schools. No significant differences are found in internalising problems according to the level of academic achievement from both teachers’ and students’ perspectives. Generally, students who are well-adapted to the school context have the least symptoms of internalising problems compared to average and less-adapted groups from the teachers' perspective. In addition, from students’ perspectives, adolescent females present more internalising problems than males. Finally, teachers rated fewer internalising problems when compared to the students. In conclusion, the low level of awareness of teachers towards the internalising problems of students arouse attention. It is suggested that teachers should attend professional development programs in order to address to students’ internalising problems
Keywords: Internalising problems; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; academic achievement; gender differences; school adaptation

"The Never-Ending Task": A case study on Performing Arts with People with Intellectual Disabilities in Macau - Carol, Wong Weng Si (University of Saint Joseph, 2023)

THE RELATIONSHIP BETWEEN PSYCHOPATHOLOGY AND RESILIENCE OF SECONDARY SCHOOL STUDENTS IN MACAO - Chan, Ngan Ieng (University of Saint Joseph, 2023)
School-age children and adolescents face several psychological conditions frequently associated with negative consequences on behavioral and mental problems. Their level of mental resilience may affect their responses to academic or interpersonal issues and coping with challenges, which in turn affects their mental health. This study aims to characterize the current status of the psychopathology and resilience of secondary students and to analyze the relationship between psychopathology and resilience in a sample of 80 girls aged 12–18 was selected by cluster sampling from one private secondary school with six grades in Macao. In this study, we used the Achenbach System of Empirically Based Assessment (ASEBA) to assess behavioral and emotional problems and the Resilience Scale for Chinese Adolescents to assess resilience. A total of 78 valid questionnaires were obtained for CBCL, 78 for TRF, 80 for YSR, and 77 for Resilience Scale and data were analyzed by using SPSS. The results reveal that clinical prevalence of Total Problems (YSR, 27.5% > CBCL, 19.2% > TRF, 15.4%) and Internalizing Problems (YSR, 22.5% > CBCL, 17.9% > TRF, 11.5%) from the perspective of adolescents was higher than that from the perspectives of parents and teachers. Senior students exhibited higher frequency on the borderline clinical range than Junior students. (χ2(2, N=80) =14.56, p<.001). The average score of resilience is 3.24±0.51, which is above the middle level. Regarding the YSR scale and Resilience scale, we found that the score of Affect Control is significantly negatively correlated with the score of Internalizing Problems (r = -.354, p<.01). Family Support is also significantly negatively correlated with the score of Internalizing Problems (r = -.302, p<.01). Good affect control and family support can reduce various emotional and behavioral problems. The results of the study found the resilience level can negatively affect internalizing problem behaviors and externalizing problem behaviors. The results are promising and can give clues for preventing and promoting measures regarding mental health issues to both family and school education contexts, as creating a sustainable development strategy of improving adolescents’ mental resilience quality
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; psychopathology; resilience; secondary students

Gender Differentiated Parenting and Family Characteristics Affecting Parent-Adolescent Relationship in Macao: Che Iok Seng a.k.a Matthew - Che, Iok Seng (University of Saint Joseph, 2023)
This study aims to investigate gender-differentiated parenting and the factors that affect parent-adolescent relationships in Macao families. The study will address the following research questions: A) Does gender-differentiated parenting exist in Macao families? B) How does the academic level of parents relate to conflict resolution and acceptance levels? C) How does the length of time parents have lived together relate to conflict resolution and acceptance levels? D) How does the sibling position of adolescents relate to conflict resolution and acceptance levels? The study employed a quantitative research approach with a purposive and convenient sample of parents with children aged between 12 to 18 years old in Macao. The data were collected using the Parent-Child Interaction Questionnaire—Revised-Parent version (PACHIQ-R-P) through a questionnaire survey from May to August 2022. Out of the 172 completed questionnaires, seven were invalid, resulting in 165 valid questionnaires. The findings showed that gender differentiation in parenting was confirmed, with significant results showing that fathers had lower acceptance and conflict resolution levels when their child was a boy. Mothers showed similar acceptance and conflict resolution levels regardless of their child's gender. Furthermore, the study found that parents' acceptance of their children was influenced by their academic level, length of time living together, and the child's sibling position. This study is the first of its kind in Macao and could provide valuable insights for family and adolescent services in the region
Keywords: Adolescents; Conflict Resolution; Gender differences; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

TO EXPLORE SMOKING BEHAVIORS OF ADULTS IN MACAO: DISCOVERIES BY QUANTITATIVE AND QUALITATIVE STUDIES - Dias, Luis Borges (University of Saint Joseph, 2023)
The purpose of the study was to explore the smoking behaviour of the smokers living in Macao. I was part of the 1st group of doctors to have chosen to initiate smoking cessation in Macau. In addition to my diverse academic background of study in laws- a dissertation about the effect of tobacco control program in Macao (submitted in 2011), a master in Public Administration, and five years of working experiences as an Inspector Assistant of tobacco, I had the conviction that I have to write to share my experience and knowledge about smoking cessation to contribute to the field of counselling and psychotherapy as there is little research data concerning smoking prevalence and demographics in Macao. This study consists of two parts – PART I presents the quantitative data collected by a questionnaire-survey over 1378 smokers and PART II qualitative data from semi-structured interviews with 10 adult smokers to explore their experiences of smoking and smoking cessation in Macao. Quantitative data analysis was conducted with the SPSS, while qualitative analysis with coding and theme identification by following the grounded theory procedures. The study found that about 85% smoker surveyed consumed more than half a pack of cigarette per day and about 31% reported various symptoms like irritability, fatigue, loss of appetite and difficulties in concentration. The qualitative study has identified major positive factors related to initiation and maintenance of smoking cessation, namely health concerns, financial concerns and family support. Major negative factors related to relapse of smoking are peer influences, smoking of family members, and impacts of stressful life events. Based on findings of the study, it is argued that preventive anti-smoking education should be implemented among young people. Promotion of health education and preventive anti-smoking strategist and policy in Macao are discussed. The data collected indicate the fact that individuals who have pathologies of the cardiovascular system as a motivating factor for contemplating or taking actions for smoking cessation. Moreover, financial problems, gender (male predominantly), married with family support, higher educational level, without psychological diseases, better economic status, lower nicotine dependent are predictors to success in quit smoking. It also raises the possible need to deepen some evaluation parameters hither to be only superficially addressed. Therefore, and by limitations inherent to the study, this hypothesis needs further investigation. I argue that non-pharmacological treatment methods alone have proven to be effective in the smoking cessation process. However, it is argued that this combined with pharmacological therapy, in particular in specialized consultations, would be more effective and capable in increasing success rates in smoking cessation
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; grounded theory; relapse; smoking behaviour; smoking cessation

Primary teachers' burnout at the inclusive education schools in Macao - Ieong, Iek Kuan (University of Saint Joseph, 2023)
"In 2021/2022 academic year, there are 2,244 SEN students in Macau and its growth rate is 36% in ten years. However, at the present, there are 38 schools providing the related education to them. Admittedly, this is an unbalanced supply and demand. In fact, the teachers who work at inclusive education schools are bearing all responsibility to teach SEN students and their mental health is worth to attention. Moreover, there are 1,224 SEN students in primary (2021/2022 academic year), it accounting for 55% of all. That is, the numbers of their teachers are the most and they are representative. Therefore, exploring primary teachers’ burnout at inclusive education schools becomes the topic of this study, even more important, it is including to compare normal and resource teachers. This topic is rarer currently in Macau. On the one hand, emotional exhaustion, depersonalization and (reduced) personal accomplishment are dimensions of burnout (Maslach et al., 1996). These become the dependent variables of this study. According Ecological Systems Theory (Bronfenbrenner, 1979) and the factors of self-efficacy in inclusive education (Sharma et al., 2012), the following hypotheses are provided to guide this study: (1) normal teachers’ emotional exhaustion, depersonalization and reduced personal accomplishment are higher than those in resource teachers; (2) teachers’ attitudes into inclusive education, (3) teachers’ self-efficacy to use inclusive instruction (SEII), (4) teachers’ self-efficacy in collaboration (SEC) and (5) teachers’ self-efficacy in v managing behavior (SEMB) both are negatively related to emotional exhaustion, depersonalization and reduced personal accomplishment; (6) teachers’ stress of Covid19 is positively related to emotional exhaustion, depersonalization and reduced personal accomplishment. On the other hand, quantitative methodology, and snowball sampling are used in this research. At last, 132 responds are collected, including 100 normal teachers and 32 resource teachers. They are from 48 inclusive education schools in Macau. All data were analyzed by SPSS 25.0. The results of this study are followed: (1) teachers’ emotional exhaustion level is middle, their depersonalization and reduced personal accomplishment levels both are low; (2) resource teachers’ emotional exhaustion and depersonalization are higher than normal teachers; (3) teachers’ attitudes into inclusive education negatively related to depersonalization but positively related to reduced personal accomplishment; (4) in the factors of self-efficacy, only SEII is negatively related to reduced personal accomplishment; (5) teachers’ stress of Covid-19 is positively related to emotional exhaustion, depersonalization and reduced personal accomplishment."
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

ORGANIZATIONAL JUSTICE AND PSYCHOLOGICAL WELL-BEING AMONG HEALTHCARE WORKERS IN MACAO - Kaewmanee, Celina dos Santos (University of Saint Joseph, 2023)
This study examined the relationships between organizational justice, job satisfaction, and subjective well-being of medical doctors and nurses in Macao. It applied a quantitative methodology through a cross-sectional applying self-response questionnaires to 149 healthcare workers. Consistent with the group-engagement model (Tyler & Blader, 2003), findings indicate that organisational justice and job satisfaction improve subjective well-being. Yet, inconsistent with the model and our hypotheses, organizational justice did not affect work satisfaction. Finally, nurses experienced less positive justice perceptions than doctors. The study provides insights into the relationship between organizational justice, job satisfaction, and subjective well-being among healthcare professionals, which might help enhance working conditions. Healthcare organizations should prioritize promoting job satisfaction and justice perceptions to increase healthcare personnel's subjective well-being. The cross-sectional design limits causal inferences about variable relationships, and the self-reported data may have social desirability or response biases. Still, the originality and value of this paper lie in its contribution to the literature on the well-being of healthcare workers, particularly in the unique context of Macao. To our knowledge, this is the first study in Macao to examine the relationship between organizational justice, job satisfaction, and subjective well-being among healthcare workers
Keywords: Healthcare; Job Satisfaction; Organizational Justice; Subjective well-being; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

THE MODERATING EFFECTS OF POWER DISTANCE ON THE RELATIONSHIP BETWEEN PERCEPTIONS OF ORGANISATIONAL POLITICS AND ORGANISATIONAL JUSTICE - Kong, Fion Ming Ying (University of Saint Joseph, 2023)
The aim of this research is to investigate how power distance orientation effects the relationship between perceptions of organisational politics and perceptions of organisational justice. A quantitative cross-sectional study was conducted on 172 full time workers in Macau, where respondents self-responded to questionnaires that were translated back-to-back into Chinese in order to accommodate the populations native language. This study found that power distance was contrary to our initial hypothesis of high-power distance equals to high politics and low justice. It was found that high power distance in facts equates to lower political perceptions and higher justice perceptions. This study contributes to understanding power distance in Macau as it is not noted in the Hofstede cultural dimensions. We also learned that having a longer distance between a position of power can contribute to less political activity and more sense of justice for the employees
Keywords: Organisational Justice; Organisational Politics; Power Distance; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

Externalizing Behaviour in Macao: Gender and Parental Participation - Kuok, Oi Lou (University of Saint Joseph, 2023)
There are gaps in the research on gender differences and parental participation and the interaction between gender and parental participation in non-Western cultural contexts, particularly the Macao context. The current study aims to fill these gaps by examining gender and parental participation (i.e., father only, mother only, or both) differences and interactions in externalizing behaviour (oppositional defiant disorder and conduct disorder) during late childhood and adolescence (i.e., from age 10 to 18) in Macao. The methodological approach for the current study was a cross-sectional design with a quantitative methodology based on self-rated questionnaires. In certain items, we did discover gender differences. More boys than girls appeared to concur that they occasionally misbehave at school or start fires. And it appeared that girls were more likely than boys to concur that they occasionally exhibit unexpected mood or emotion changes and strong tempers. The children in the groups where only the mother or father participated tended to agree more than they prefer to hang out with older kids than kids their own age. This is in contrast to the group with more parental participation, which is represented by both parents submitting the questionnaire. Although none of the hypotheses proposed were supported, our outcomes implied culture and subculture may play important roles on youths’ externalizing behaviour
Keywords: Externalizing behaviour; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; gender; parental participation

FEMALE EMPLOYEES’ PERCEPTIONS OF WORK-LIFE BALANCE AND TURNOVER INTENTIONS IN MACAO - Lei, Hon Nei; Silva, Maria Rita (University of Saint Joseph, 2023)
"This study explored the relationships of work-life balance and turnover intentions of full-time employees in Macao, and role of gender, parenting, and elderly care. Namely: (1) What is the relationship between work-life balance perceptions and turnover intentions? (2) What is the moderating role of gender in the relationship between work-life balance perceptions and turnover intentions? (3) What is the moderating role of parenting (i.e., having children or not) in the relationship between work-life balance perceptions and turnover intentions? And, (4) what is the moderating role of care for elderly family members (i.e., having to provide care or not) in the relationship between work-life balance perceptions and turnover intentions?"
Keywords: Elderly Care; Gender; Parenting; Thesis and Dissertations Master of Organisational Psychology (MOP); Turnover Intention; University of Saint Joseph; Work-Life Balance

Do job satisfaction and supervisory support affect burnout among security guards in Macao? - Leong, Chi Ian (University of Saint Joseph, 2023)
We see security guards around in Macao in our daily lives and they are the ones who are responsible for protecting people’s safety and properties. Most security guards are non-local workers and might have different workplace stress levels. This study’s main aim is to investigate how job satisfaction and supervisory support are related to burnout among security guards in Macao. The research is carried out through a quantitative questionnaire to collect data and deliver it to the local and non-local security guards working in Macao. A total of 132 questionnaires were collected. It is expected that when security guards have higher job satisfaction and more supervisory support, they will experience less burnout. This intention enables the organization to make some changes to help the security guards from burnout due to job dissatisfaction and no supervisory support. The practical implication for reducing stress is introducing training courses such as mindfulness-based stress training programs. Future research will investigate other support like organizational support, peer support, and family and friends support on security guards
Keywords: Burnout; Job satisfaction; Supervisory support; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

Can The Organisation Help? Exploring The Relationship Between Emotional Intelligence, Resilience And Burnout Among Counselling Professionals With Organisational Socialisation As Moderator - Mak, Sin Kei (University of Saint Joseph, 2023)
The phenomenon of burnout has been recognised as a worldwide occupational health issue after being vastly studied for decades. Trait Emotional Intelligence (trait EI) and resilience have been identified as personal protective factors (Gutierrez & Mullen, 2016; Listopad et al., 2021), while organisational socialisation is suggested to be an organisational factor in helping people in preventing burnout (Taormina & Law, 2000). With the purpose of 1) investigating the phenomenon in the counselling profession, as well as 2) exploring how trait EI and resilience are related to burnout and whether organisational socialisation might impose moderating effects in between, the present study examined 115 counselling professionals currently employed and working in organisational settings in Macau by snowball sampling, using a quantitative and cross-sectional approach through self-reported online questionnaires. From the data obtained, different burnout patterns were observed according to job titles and work settings, indicating that counselling professionals with different specialties and work in different settings have unique sources of stress, which resulting in differences in their burnout patterns. No between-group differences were observed in age and work experience, while male participants have a higher burnout perception than female participants in the current study. On the other hand, current results suggested trait EI and four components of resilience (determination, endurance, adaptability and recuperability) are negatively correlated to counselling professionals’ burnout perception, providing supportive evidence that trait EI and resilience are protective factors against burnout. Moderation analysis results revealed that organisational socialisation has some moderating effects on the relationship between trait EI, resilience and burnout. However, differences in direction and intensity indicated that the moderating effects of organisational socialisation might be influenced by individual differences. Further studies are needed to better the understanding of the moderating effect of organisational socialisation. Limitations of the current research and implications for counselling professionals and organisations were also discussed in the study
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; burnout; counselling professionals; organisational socialisation

MULTICULTURAL CAREGIVER TEAMS IN ELDERLY CENTRES IN MACAO: COMMUNICATION AND PERCEIVED SERVICE QUALITY - Mejia Dominguez, Victor Alejandro (University of Saint Joseph, 2023)
This study explored the effect of communication (i.e., among staff, and between staff and clients) and of cultural diversity on job satisfaction (i.e., intrinsic, extrinsic, and general) and perceived service quality of formal caregivers working in elderly services in Macao. We applied a quantitative methodology, based on a cross-sectional design using a self-response questionnaire to 162 staff in six elderly centres in Macao. Based on an extensive review of the literature, we proposed that: H1) cultural diversity is negatively related to (a) intrinsic job satisfaction, (b) extrinsic job satisfaction, (c) general job satisfaction, and (H5) negatively related to perceived competence and service quality; (H2) communication (a) among staff and (b) between staff and clients is positively related to intrinsic job satisfaction (H3) extrinsic job satisfaction, (H4) general job satisfaction, and (H6) perceived service quality; and finally that (H7) intrinsic, (H8) extrinsic, and (H9) general job satisfaction mediate the relationship between (a) cultural diversity, (b) communication among staff and (c) communication between staff and clients, and perceived service quality. We found that more communication among staff was related to higher intrinsic, extrinsic and general job satisfaction, and perceived competence and service quality. And intrinsic job satisfaction mediated the positive effect of communication among staff on perceived service quality. Opposite to predicted communication between staff and clients was related to lower levels of job satisfaction. And cultural diversity was positively related to satisfaction, as well as perceived competence and service quality. The theoretical and practical implications of findings, as well as limitations and suggestions for future research were discussed
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; caregivers; communication; elderly services; job satisfaction; multicultural teams; service quality

SOCIAL PERSPECTIVES ABOUT CANTONESE OPERA IN MACAO ACROSS GENERATIONS: CULTURAL IDENTITY AND SOCIAL BONDING - Sin, Shuk Ching; Silva, Maria Rita (University of Saint Joseph, 2023)
"Cantonese opera (CO) represents an art form that had its golden time in Macao during the mid-twentieth century. CO still has many loyal fans but they mainly are in the older generation. The purpose of this study was to explore if CO is considered a cultural capital heritage in Macao, related to cultural identity and transmitted across generations to support social bonding. Applying a qualitative methodology, a script for exploring participants’ experiences and opinions about CO was designed, and different groups of individuals were recruited for semi-structured interviews and focus groups. The data collected was analysed by a thematic analysis of the verbatim transcripts. Findings show that in the past first contacts with CO happened in family and related social context, mainly during participants’ developing age. However, currently CO is no longer passed on to the next generation. Despite that the young generations acknowledging their cultural identities in CO, mainly in terms of Cantonese culture and Cantonese language, older individuals engaged with CO seemed to perceive their cultural identities more in depth in its history, literacy and music. Actually, engagement is an important factor that generates social bonds. The CO leisure practitioners, no matter young or old, experienced the effects of social bonding during the ritual of enquiry in the process of learning and practising CO. To improve CO’s preservation in Macao, the adoption of strategies such as developing new productions, crossover with other media, innovations in promotion targeting the young audiences, and absorbing audiences in the Great Bay area were proposed. Finally, the potential use of CO as a tool in counselling and community work is discussed. "
Keywords: Cantonese Opera; Cultural Identity; Individual Well-being; Social Bonding; Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

Emotional Support Influence Work Engagement and Mental Well-being in Macau: The Moderating Effect of Self-reflection - Sou, Kam Chan; Kuok, Angus C. H. (University of Saint Joseph, 2023)
The purpose of this study is to examine work engagement and mental well-being in Macau, specifically after more than three years of COVID. Examine whether external factors such as emotional support from supervisors, co-workers, and family members have a positive impact on work engagement and mental well-being, and whether the internal factor self-reflection with its three aspects of need for self-reflection, engagement in self-reflection, and insight from self-reflection moderates the relationship between emotional support, work engagement, and mental well-being. The target audience consists of Macau's integrated resort, hospitality, and gaming industry employees. According to the Affective Event Theory (AET), affective events at work generate emotional responses that influence the attitudes and behavior of employees in the workplace. In this study, this theoretical framework was used to clarify the interplay of variables that explain emotional support from supervisors, co-workers, and family members, work engagement, and mental well-being. An online self-response survey (N=325) was used to conduct quantitative and cross-sectional research. There was also a combination of simple random sampling, convenience sampling, and referral sampling. All variables were found to be correlated, and while perceived supervisor support was a significant predictor of all aspects of work engagement and mental well-being, family and co-worker support only predicted certain aspects of these variables. Self-reflection partially moderated the positive effects of certain emotional support on work engagement and mental well-being
Keywords: Co-worker Support; Emotional Support; Family Support; Mental Well-being; Perceived Supervisor Support; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; Work Engagement

LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE INFLUENCE ON EMPLOYEES’ ORGANIZATIONAL COMMITMENT UNDER THE PANDEMIC SITUATION - Sun Leung, Wai Chai (University of Saint Joseph, 2023)
The aim of this study is to investigate the influence of leadership styles and organizational cultures to employee’s organizational commitment under the pandemic situation in Macao. The dependent variables comprise of the three dimensions of organizational commitment. Among those three, affective commitment and continuance commitment are considered to be analyzed in this study. The leadership styles concept and organizational cultures are applied as the independent variables. The objectives are achieved using quantitative research method with questionnaires in Likert scale scores. The two significance reveals that laissez-faire leadership style had a positive relationship with continuance organizational commitment (H4) and innovative culture had a positive correlation with continuance organization commitment (H6). Such outcomes were extended to a qualitative study with qualitative approach on discourse analysis to explore the potential factor and a leadership discourse analysis was initiated. While the findings on influence of leadership and culture on organizational commitment is not a major concern for Macao employees in the pandemic situation, the significance of specific leadership style and culture rationalizes the transformation and status of Macao employees’ views towards leadership and employers’ perspective on organizational culture. The data collected in this study may also provide valuable resources for future study and training programs for the coming batch of employees in the coming new phase of Macao in entering the 2nd round of gaming licensing. Create the right leadership and culture for the organization to bring back the passion of Macao employees
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

THE RELATIONSHIP BETWEEN PARENTING STYLES, ACADEMIC ACHIEVEMENT AND BEHAVIORAL PROBLEMS OF PRIMARY STUDENTS IN MACAO - Tang, I. Sam (University of Saint Joseph, 2023)
"Parenting styles may have various effects on children’s development and educational outcomes, particularly a relationship with behavioral problems and academic achievement. This study examines the relationship of between parenting styles, behavioral problems and academic achievement. A cross-sectional and questionnaire-design (Parenting Style Scale (Saunders et al., 2013); Strength and Difficulties Questionnaire (Goodman & Goodman, 2009; Goodman, 1999; Goodman, 1997)) study was used with a sample total of 98 parents with the eldest child of the family aged between six to twelve. Results of the findings are mainly inconsistent with the majority of literature. Indulgent and authoritative parenting are the predominant parenting styles, yet parenting styles does not relate to academic achievement. On the other hand, the correlation between behavioral problems, specifically prosocial behaviors and academic achievement are moderate. Furthermore, there is no difference between the type of behavioral problems according to gender. In further studies, a larger sample size, teachers and students as informants, and the inclusion of the analysis of other factors that could be influencing parenting styles, behavioral problems and academic achievement are suggested to be considered. "
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

THE EFFECTS OF TEACHER SELF-EFFICACY AND PERCEIVED AUTONOMY ON TEACHER WORK ENGAGEMENT: THE MEDIATING EFFECT OF PERCEIVED ORGANISATIONAL SUPPORT - Wan, Sok Leng (University of Saint Joseph, 2023)
The aims of the present study are to investigate the level of work engagement of the inclusive teachers in Macau and what potential factors would contribute to the increase of their level of work engagement. In this research, the framework of the self-determination theory developed by Ryan and Deci in 2000 was partially employed. I suggested the inclusive teachers’ self-efficacy and perceived autonomy to act as the independent variables, while perceived organisational support was involved as the mediating variable. Quantitative method was applied in this study by using an online self-response questionnaire (N= 150). The stratified sampling strategy was applied as well in order to ensure the representativeness. No gender difference of work engagement level was found among Macau inclusive teachers. Positive correlations were found among all variables. Besides, perceived organisational support was expressing positive mediating effects on the relationships between independent and dependent variables under some specific circumstances. For example, the relationship between efficacy to use inclusive instructions and emotional and physical work engagement; the relationship between perceived autonomy and cognitive, emotional, and physical work engagement. Theoretical and practical implications for the non-tertiary schools and inclusive teachers can be found in this study. Future studies should be continued to investigate the limitations and suggestions of this field of research
Keywords: PERCEIVED ORGANISATIONAL SUPPORT; TEACHER PERCEIVED AUTONOMY; TEACHER SELF-EFFICACY; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; WORK ENGAGEMENT

PSYCHOMETRIC PROPERTIES OF BASIC FAMILY RELATIONS INVENTORY (BFRI) IN MACAO - Chan, Kuai Ian (University of Saint Joseph, 2024)
By discussing various aspects of family functioning, including the intricate nature of family functioning, family dynamics’ impact on adolescent growth and lifelong development, and the COVID-19’s effects on family relationships, it reveals the importance and necessity of assessment instruments in the field of family counselling. And concerning the gap between family research and clinical practice as well as the absence of a singular tool capable of evaluating various family functions comprehensively in the Macao context, the study introduced the Basic Family Relations Inventory (BFRI; or ‘Cuestionario de Evaluación de las Relaciones Familiares Básicas’, CERFB), a self-reported questionnaire based on Linares’ Basic Family Relations Theory. This valuable tool consists of 25 items, assessing simultaneously the quality of family relationships in two basic dimensions—marital and parental functioning. This study aimed to develop the Chinese version of the BFRI and investigate its psychometric properties in the context of Macao. By employing a quantitative research approach, it evaluated the normal distribution, exploratory factor analysis and reliability of the BFRI in a non-clinical snowball and convenience sample of 165 participants with at least one biological child from 12 to 18 years old. In the exploratory factor analysis, the initial factor extraction resulted in four components, reflecting both marital and parental items. This suggested potential overlap and interconnectedness between the marital and parental subsystems. Subsequent analysis identified a three-factor solution, separating marital, negative parental, and positive parental components. This aligned with the factor structure of the original Spanish version of the BFRI. A two-factor solution was also explored, replicating findings from the previous Italian and Portuguese validation of the BFRI despite some inconsistencies in item alignment. The EFA results revealed that the three-factor structure of the Chinese version of the BFRI was the best fitting model for the Macao population. Reliability analysis, assessed through Cronbach’s alpha, indicated satisfactory internal consistency of the scales. The results of the analyses demonstrate promising psychometric properties, supporting the tool’s effectiveness in assessing marital and parental relationships in a Macao population. The study contributed to the development of the valuable family assessment instrument. It suggested that the Chinese version of the BFRI could serve as a useful instrument to concurrently assess the quality of marital and parental relationships and systematically collect the data of family functioning in both dimensions. It’s also believed that this instrument could benefit the evaluation of family dynamics and comprehension of family relations not only in family research studies, but also in counselling intervention and clinical therapy, preventing risks to the health of children as well as promoting healthy family contexts in Macao
Keywords: Basic Family Relations Inventory (BFRI); Marital relationship; Parental relationship; Psychometric properties; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph